2009
DOI: 10.1021/jf900164h
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Leu7-Surfactin from the Endophytic Bacterium Bacillus mojavensis RRC 101, a Biocontrol Agent for Fusarium verticillioides

Abstract: Bacillus mojavensis is an endophytic bacterium patented for control of fungal diseases in maize and other plants. Culture extracts and filtrates from this bacterium were antagonistic to the pathogenic and mycotoxic fungus Fusarium verticillioides. However, the identity of the inhibitory substance from extracts of this bacterium has not been determined. An HPLC-MS analysis of the culture filtrate showed a major ion peak that was identified as a cyclic lipopeptide. Furthermore, collisional ion dissociation (CID)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 29 publications
1
54
0
1
Order By: Relevance
“…24 A Leu 7 -surfactin antagonistic to F. verticillioides has also been reported. 25 Mojavensin A produced by Bacillus mojavensis B0621A Zongwang Ma et al Fumonisin, especially fumonisin B 1 , can increase the incidence of neural tube defects and inhibit eukaryotic protein synthesis, and it can also be a potential threat to human health. 26,27 In vitro antifungal experiments indicated that anteiso-C15 mojavensin A (1) and the two fengycins (2 and 3) had dose-dependent antagonistic activity against F. verticillioides and other phytopathogens.…”
Section: Structure Elucidationmentioning
confidence: 99%
“…24 A Leu 7 -surfactin antagonistic to F. verticillioides has also been reported. 25 Mojavensin A produced by Bacillus mojavensis B0621A Zongwang Ma et al Fumonisin, especially fumonisin B 1 , can increase the incidence of neural tube defects and inhibit eukaryotic protein synthesis, and it can also be a potential threat to human health. 26,27 In vitro antifungal experiments indicated that anteiso-C15 mojavensin A (1) and the two fengycins (2 and 3) had dose-dependent antagonistic activity against F. verticillioides and other phytopathogens.…”
Section: Structure Elucidationmentioning
confidence: 99%
“…The biosurfactant produced by microbes are helpful in bioremediation of heavy metal, pesticides and hydrocarbon contaminated sites (Juwarkar et al, 2008). They are also used as biocontrol agent to protect plant against various diseases resulting in higher crop yields (Asaka and Shoda, 1996;Krishnayya and Grewal, 2002;Gravel et al, 2005;Snook et al, 2009;Hultberg et al, 2010). Based on their functional characteristics they have much more potential to be used in agriculture i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A series of b-and y-type ions were detected, and a peptide sequence was deducted from this CID spectrum by MassBioLynx-Peptide Sequencing. Seven amino acids (Glu-Leu-Leu-Val-Asp-Leu-Leu) were determined by ESI-MS/MS in four precursor ions (figures of ESI-MS-MS spectra of the precursor ion not shown), agreeing with the CID fragmentation of the surfactin standard (Lim et al, 2005;Snook et al, 2009). The patterns of m/z 1058.31 [M+Na] + of y-Max, determined by ESI-MS mass spectrometry, are shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Its mode of action is based on its detergent-like activity in dissolving several types of lipid membranes (Snook et al, 2009). B. subtilis strain can modulate host resistance associated with differential gene expression in tomatoes and cucumbers and can trigger the plant defense machinery to enhance resistance to fungal pathogen ingress.…”
Section: Discussionmentioning
confidence: 99%